WASTE MANAGEMENT WITH BLACK SOLDIER FLY (BSF) FOR SUSTAINABILITY DEVELOPMENT IN WEST BANDUNG REGENCY - Andri Yulianto; Bernard Hasibuan; Sugiarto Sugiarto (Jurnal Bisnis Manajemen, 2023)
This study aims to explore the concept of household waste management using the BSF larvae method that is claimed to be able to reduce organic waste piles that have the potential to cause disease and reduce the beauty of the environment in Padalarang District, West Bandung Regency. descriptive and exploratory qualitative analysis are employed to examine the relationship between stakeholders in managing waste associated with the theory of management functions according to GR Terry so that the system that has been running with BSF media can reduce the volume of landfill waste.Six respondents were interviewed with in-depth interviews so that this study obtained the information needed to explore the concept of waste management